PERFORMANCE OF SOCIAL AGENCY ON HANDLING THE HOMELESS in MANADO CITY - RIMBING, GRACELLA; LENGKONG, FLORENCE DAICY; POMBENGI, JERICHO (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This research is a qualitative research to examine the performance of Manado City Social andCommunity Empowerment Agency in handling the homeless in Manado City, using performance indicatoraccording to Dwiyanto: Productivity, Service Quality, Responsiveness, Responsibility, and Accountability.Data were obtained through interviews, completed with secondary data, in the form of data from theManado Social Service and Manado city newspapers. The number of informants in this study is 7 people,consisting of: 2 employees of Manado City Social Service, 3 homeless people located in Manado city, and 2people who often see the daily life of the homeless. From the results of the research, obtained; (1) In termsof productivity, the performance of Manado City Social and Community Empowerment Agency in handlingthe homeless is still minimal. (2) In terms of service quality, the performance of Manado City Social andCommunity Empowerment Agency in handling the homeless is still minimal. (3) In terms of responsiveness,the performance of Manado City Social and Community Empowerment Agency in handling the homelessin Manado is still minimal. (4) In terms of responsibilitas, Manado City Social and CommunityEmpowerment Agency in handling the homeless is quite enough. (5) In terms of accountability, theperformance of Manado City Social and Community Empowerment Agency in handling the homeless isquite enough.Keyword: Performance, Social Agency, Homeless